Outcomes of two quality improvement implementation interventions for depression services in adults with substance use problems. (3rd March 2020) - Morton, Isabella; Hurley, Brian; Castillo, Enrico G.; Tang, Lingqi; Gilmore, James; Jones, Felica; Watkins, Katherine; Chung, Bowen; Wells, Kenneth
ABSTRACT: Background : Comorbid depression and substance use disorders (SUDs) are associated with poor health and social outcomes disproportionately affecting under-resourced communities. Objectives : To test the hypothesis that a coalition approach to collaborative care (CC) for depression would improve outcomes of hazardous drinking and behavioral health hospitalizations, relative to technical assistance, for individuals with comorbid substance use problems. Substance use problems were defined by meeting criteria for DSM-IV substance abuse or dependence, hazardous drinking by AUDIT-C, or treatment in a SUD program within the prior 6 months. Methods : Two depression CC implementation approaches were compared: Resources for Services (RS) provided expert technical support for CC toolkits to individual programs. Community engagement and planning (CEP) supported multi-sector coalitions in collaborating in planning, adapting, implementing and monitoring CC toolkits. One thousand eighteen individuals with depression (PHQ-8 ≥10) enrolled. Regression analyses estimated intervention effects in participants with comorbid substance use problems (n = 588, 281 females, 307 males). Substance use problems were defined by meeting criteria for DSM-IV substance abuse or dependence, hazardous drinking by AUDIT-C, or treatment in a SUD program within the prior 6 months. Results : There were no significant baseline differences by intervention status among participants with depression and substance use problems. Intervention effects on primary outcomes including depression were not significant at 6 months. Compared to RS, CEP significantly reduced alcohol consumption (CEP = 1.6, RS = 2.1, p = .038), probability of behavioral health hospitalizations (OR = 0.50, p = .036), and use of specialty mental health visits (IRR = 0.52, p = .027), while increasing use of faith-based depression services (IRR = 3.4, p = .001). Conclusions : Given feasibility and possible benefits, CEP should be considered a promising approach to implementing depression CC with potential benefits to adults with comorbid substance use problems.